2020
DOI: 10.1166/jbt.2020.2492
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of a Multi-Functional Hydrogel from a Branched Peptide Amphiphile and Its Effects on Bone Marrow Mesenchymal Stem Cells

Abstract: In this work, a branched peptide amphiphile (B-PA) presenting RGD and IKVAV motifs was fabricated by solid-phase peptide synthesis and self-assembled into a nanofiber hydrogel in which rabbit bone marrow mesenchymal stem cells (BMSCs) were seeded and cultured for seven days. Specifically, 1 wt% B-PA was self-assembled into a nanofiber hydrogel with the addition of culture medium and observed using transmission electron microscopy. The B-PA with a molecular weight of 2191.72 and a purity >95% self-assembled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This was further correlated with increased expression of MSC integrins [21] . Recently, a branched peptide amphiphile (B−PA) containing RGD and IKVAV was designed by Yixiu et al [22] . The authors judiciously employed nanofibrous hydrogel as a suitable matrix for the growth of bone marrow‐derived mesenchymal stem cells [22] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was further correlated with increased expression of MSC integrins [21] . Recently, a branched peptide amphiphile (B−PA) containing RGD and IKVAV was designed by Yixiu et al [22] . The authors judiciously employed nanofibrous hydrogel as a suitable matrix for the growth of bone marrow‐derived mesenchymal stem cells [22] .…”
Section: Introductionmentioning
confidence: 99%
“…[21] Recently, a branched peptide amphiphile (BÀ PA) containing RGD and IKVAV was designed by Yixiu et al [22] The authors judiciously employed nanofibrous hydrogel as a suitable matrix for the growth of bone marrow-derived mesenchymal stem cells. [22] It has been observed that the IKVAV sequence plays a major role in angiogenesis and re-epithelialization, two essential processes involved in the wound healing. [14,23] In addition to promoting neuronal cell differentiation, inhibiting astrocyte differentiation, and improving cell growth, IKVAV also induces fibril formation in self-assembled structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation